A Cell Membrane‐Targeting Self‐Delivery Chimeric Peptide for Enhanced Photodynamic Therapy and In Situ Therapeutic Feedback. Issue 1 (25th November 2019) - Ma, Wen; Sha, Sui‐Nan; Chen, Pei‐Ling; Yu, Meng; Chen, Jian‐Jun; Huang, Chao‐Bo; Yu, Bin; Liu, Yun; Liu, Li‐Han; Yu, Zhi‐Qiang
Abstract: Nowadays, cell membrane‐targeted therapy, which owns high antitumor efficacy by avoiding cell barriers, has received great attention. Here, a cell membrane‐targeted self‐delivery theranostic chimeric peptide CMP‐PpIX is designed for simultaneously targeted photodynamic therapy (PDT) of tumor and real‐time therapeutic feedback. Self‐assembled CMP‐PpIX nanoparticles can effectively accumulate in tumor by enhanced permeability and retention effect without additional vector. And this chimeric peptide CMP‐PpIX has low background fluorescence, which is due to its relatively high intramolecular Förster resonance energy transfer (FRET) quenching efficiency between 5(6)‐carboxyfluorescein (FAM) and 4‐(dimethylaminoazo)‐benzene‐4‐carboxylic acid (Dabcyl). More importantly, CMP‐PpIX can be anchored on the tumor cell membrane for more than 8 h. Under irradiation, reactive oxygen species produced by CMP‐PpIX directly damage cell membrane and rapidly induce apoptosis, which significantly improve the efficacy of PDT in vitro and in vivo. Then, peptide sequence Asp‐Glu‐Val‐Asp (DEVD) is subsequently cleaved by activated caspase‐3 and activated caspase‐7, which separates the FAM and Dabcyl and terminates the FRET process. Therefore, fluorescence of FAM is recovered to monitor the expression of activated caspase‐3 in vitro and in vivo to feedback real‐time PDT therapeutic efficacy. In general, a novel cell membrane‐targeted self‐delivery theranostic chimeric peptide offers new promise for effective imaging‐guided PDT. Abstract : In this work, a theranostic chimeric peptide CMP‐PpIX with self‐delivery properties is developed for cell membrane‐targeting photodynamic therapy (PDT) and exhibits greatly improved therapy efficacy in vitro and in vivo. Moreover, in situ therapeutic feedback can be realized by the caspase sensitive probe segment in CMP‐PpIX. This study offers a new promise for imaging‐guided high efficient PDT.